Network visualization in cell biology. - Dinkla, Kasper (Tsinghua Science and Technology)
Many of the processes known to take place in biological cells are analyzed in the form of different types of network. The complexity of these networks increases along with our knowledge of these processes, making their analysis more difficult. Network visualization is a powerful analysis method that will have to be developed further to deal with this complexity. This survey provides a brief overview of network visualization in general, followed by an in-depth discussion of its application to three network types specific to cell biology, namely gene regulatory, protein interaction, and metabolic networks. Finally, we discuss the difficulty of visually integrating these network types and trying to compare networks of cells that belong to different organisms.